2013
DOI: 10.1149/2.090308jes
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Reduction Activity of Vapor-Grown Platinum Nanotubes

Abstract: Supportless platinum nanotubes (PtNTs) were synthesized by the decomposition of platinum acetylacetonate vapor within anodic alumina templates at 210 • C. As synthesized, the nanotubes are nanoparticulate aggregates composed of Pt crystallites approximately 3 nm in diameter and with a range of lengths from 1 μm to 20 μm. Annealing treatments result in crystallite growth and morphological evolution of the tubular nanostructures including the development of nanoscale porosity. In rotating disk electrode measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 21 publications
4
28
0
Order By: Relevance
“…Starting with the seminal work of Gloaguen et al (1), a number of papers have reported on the activity of various electrocatalysts measured as thin film RDEs with a few refinements of the technique over a couple of decades. (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The RDE system is very different from typical PEMFC set-ups and absolute values of electrocatalyst activity in the two systems differ significantly as expected.…”
Section: Introductionmentioning
confidence: 73%
“…Starting with the seminal work of Gloaguen et al (1), a number of papers have reported on the activity of various electrocatalysts measured as thin film RDEs with a few refinements of the technique over a couple of decades. (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The RDE system is very different from typical PEMFC set-ups and absolute values of electrocatalyst activity in the two systems differ significantly as expected.…”
Section: Introductionmentioning
confidence: 73%
“…Our group has previously vapor deposited porous platinum nanotubes using this technique, which demonstrated very high specific activity, comparable to that of bulk polycrystalline platinum, for the oxygen reduction reaction. 27 Here, we demonstrate the extended capacity of this vapor deposition method for the synthesis and thermal evolution of bimetallic nanostructures by detailing the synthesis of platinum−ruthenium nanotubes.…”
Section: Introductionmentioning
confidence: 95%
“…The sealing process causes the formation of a highly crystalline hydroxide layer on the surface of the anodic oxide, and the hydroxide layer is highly dissolution-resistant in acidic and alkaline solutions. Using these characteristic structural and chemical properties, anodic porous alumina has been widely investigated for many applications: antireflection structures [7,8], reflectors [9], memory devices [10], diodes [11], sensors [12], optical devices [13,14], nanocontainers [15], plasmonic devices [16], nano-templates [17,18], evaporation masks [19], catalyst supports [20], resist masks [21,22], and corrosion protection [23,24].…”
Section: Introductionmentioning
confidence: 99%